Folding in Single Crystals Concavity Areas during Compression; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Alferova (Alfyorova) E. A. Ekaterina Aleksandrovna (2015, 2015)
Title screen